Avaliação do catalisador (ZnO) suportado em zeólita (NaA) na degradação fotocatalítica de efluente de laticínio - Ferreira, Gerusa Albertina (2020)
The dairy industries have increased their production in recent years, mainly with the growth of the population and the high nutritional value of their products. However, they generate a high volume of wastewater with a high organic concentration which, if discarded without treatment, can cause a huge damage to the environment. As a result, research focusing on innovation in the treatment of this effluent is extremely important, and Advanced Oxidative Processes (AOPs) an application whit study potential. AOPs are chemical methods that promote oxidation of organic compounds and have aroused interest, given their photochemical stability, high efficiency and non toxic nature. This study consisted of performing the photocatalytic degradation of milk effluent using ZnO with the zeolite of the NaA type, in order to improve the conditions for the release of these effluents. For this, the physical-chemical characterization of the effluent in natura was carried out, the artificial photocatalytic degradation was carried out with a study to reduce COD, statistical analysis and ecotoxicity. The initial parameters performed in the characterization of the effluent in natura, were well above that required by the legislation, confirming the need for treatment. The COD reduction percentage for the dairy wastewater, after the application of the proposed treatment, was 68.55%, being in the range allowed by law for the wastewater disposal. The ecotoxicity analyzes resulted in a reduction of effluent toxicity, in which the lethal concentration went from 14.49% in natura to 68.12% after treatment. The results indicate efficiency in the treatment, for the analyzed parameters and are potential to achieve the.